PENINGKATAN PRODUKSI UMKM STIK IKAN CEMILAN KHAS BANGKA BELITUNG DI JALAN COKRO AMINOTO SUNGAILIAT DENGAN TTG MESIN PENGGORENG - Yuliyanto, Yuliyanto; Somawardi, Somawardi; Subhan, Muhammad; Hakim, Zikrul (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Bangka Setara is the vision and mission of Bangka Regency as stated in the 2019-2023 RPJMP. Bangka Setara means Prosperous and Noble. Especially in fulfilling material and spiritual resilience in high and even economic growth at the Community Income Level and free from poverty and equitable development between villages and cities. MSMEs are one of the government's targets in increasing Community Income. In achieving this target, the government together with Polman Babel lecturers in the Community Service (PkM) program. The 2023 PkM Program focuses on MSMEs in the Fish Stick making group on Jalan Cokro Aminoto, Sungailiat District, Bangka Regency. The aim is to increase production capacity and quality and improve the business management system for partners. The production process carried out by partners in the frying section still uses manual methods so that production capacity is limited. In addition, in terms of business management, the partners are still not optimal. The steps taken to overcome the above by the proposing team and partners agreed to increase production capacity and improve the business management system. The method used to solve production problems is by providing a frying machine driven by a low-watt electric motor to partners, while the method to overcome business management problems is by conducting short training on small industry business management. The results of this service are felt by partners to be very helpful in the production process they do. Because they can do other processes such as packaging and packing. The frying results are even with brighter colors and also reduce oil content. Increased production results and the frying process becomes faster.